Synthesis and spectroscopic studies of alkyl substituted thiourea derivatives towards the selected antibacterial activities - - Wan M. Khairul, Suskri Siti Aishah, Rahamathullah Rafizah, Ismail Noraznawati, (Universiti Pendidikan Sultan Idris, 2016)
Synthesis and spectroscopic studies of alkyl substituted thiourea derivatives towards the selected antibacterial activities by - Wan M. Khairul, Suskri Siti Aishah, Rahamathullah Rafizah, Ismail Noraznawati,